Chapter 6 Making or unmaking a movement? Challenges for civic activism in the global governance of migration - Ålund, Aleksandra (Rethinking Globalizations, 2019)
This article discusses dilemmas of global civic activism from a neo-Gramscian perspective as both subordinated and a potential challenge to hegemonic neoliberal order. With the investigational focus on the People's Global Action on Migration, Development and Human Rights (PGA) event, the space for civic activism relating to the intergovernmental Global Forum on Migration and Development (GFMD) and its associated Civil Society Days and Common Space is analysed. The article asks how the future of PGA activism may be influenced by its formalized representation within the GFMD. It posits that the PGA has landed at a crossroad between becoming a global activist counterhegemonic movement to a dominant neoliberal migration policy and being captured in a tokenist subordinated inclusion within a truncated 'invited space' for interchange. This ambiguous position jeopardizes its impact on global migration governance, discussed with reference to theories of transversal politics and issues of counterhegemonic alliance-building.